New Branch of Intuitionistic Fuzzification in Algebras with Their Applications - Samaher Adnan Abdul-Ghani; Shuker Mahmood Khalil; Mayadah Abd Ulrazaq; Abu Firas Muhammad Jawad Al-Musawi (International Journal of Mathematics and Mathematical Sciences)
The intuitionistic fuzzification in ρ-algebras about the concepts of ideals and subalgebras given with several related characterizations is considered. Some new concepts like intuitionistic fuzzy ρ-ideal (IFρi), intuitionistic fuzzy ρ-subalgebra (IFρs), ρ-homomorphism, and intuitionistic fuzzy ρ¯-ideal (IFρ¯i) are introduced and some of their descriptions are given in this work. Further, we show some applications on the family of all intuitionistic fuzzy ρ-subalgebras IFρS(R) in ρ-algebra like the binary relations ≈μ, ≈ν and Γr on IFρS(R). Also, their equivalence classes are given and studied.